Measurement of Mustahiq's Welfare Level in the ZIS Fund Distribution Program From the Viewpoint of Maqasyid Syariah: Pengukuran Tingkat Kesejahteraan Mustahiq Dalam Program Pendistribusian Dana ZIS Dalam Sudut Pandang Maqasyid Syariah - Masruroh Masruroh; Ruslianor Maika (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the measurement of the mustahik welfare level for the ZIS fund distribution program run by Lazismu Pasuruan City. And to find out whether the ZIS fund distribution program run by Lazismu Pasuruan City is based on maqashid sharia. This research was conducted using a descriptive qualitative approach. In the data collection technique there are three techniques, namely interviews, observation, and documentation. Informants in this study were recipients of ZIS funds and amil distribution of Lazismu Pasuruan City. The results showed that the ZIS fund distribution program carried out by Lazismu in Pasuruan City had not increased in improving the welfare of its mustahik. Because of the 4 (four) goals, namely targeting, program socialization, program objectives, and supervision or monitoring. Only one indicator that has improved is targeting accuracy. This shows that the ZIS fund distribution program run by Lazismu Pasuruan City is not running smoothly. Keywords: Level of Welfare, ZIS Fund Distribution Program, Maqashid Syariah